Molecular Characterization of Global Regulatory RNA Species That Control Pathogenicity Factors in Erwinia amylovora and Erwinia herbicola pv. gypsophilae - Ma, Weilei (American Society for Microbiology, 2001)
rsmB(Ecc) specifies a nontranslatable RNA regulator that controls exoprotein production and pathogenicity in soft rot-causing Erwinia carotovora subsp. carotovora. This effect of rsmB(Ecc) RNA is mediated mostly by neutralizing the function of RsmA(Ecc), an RNA-binding protein of E. carotovora subsp. carotovora, which acts as a global negative regulator. To determine the occurrence of functional homologs of rsmB(Ecc) in non-soft-rot-causing Erwinia species, we cloned the rsmB genes of E. amylovora (rsmB(Ea)) and E. herbicola pv. gypsophilae (rsmB(Ehg)). We show that rsmB(Ea) in E. amylovora positively regulates extracellular polysaccharide (EPS) production, motility, and pathogenicity. In E. herbicola pv. gypsophilae, rsmB(Ehg) elevates the levels of transcripts of a cytokinin (etz) gene and stimulates the production of EPS and yellow pigment as well as motility. RsmA(Ea) and RsmA(Ehg) have more than 93% identity to RsmA(Ecc) and, like the latter, function as negative regulators by affecting the transcript stability of the target gene. The rsmB genes reverse the negative effects of RsmA(Ea), RsmA(Ehg), and RsmA(Ecc), but the extent of reversal is highest with homologous combinations of rsm genes. These observations and findings that rsmB(Ea) and rsmB(Ehg) RNA bind RsmA(Ecc) indicate that the rsmB effect is channeled via RsmA. Additional support for this conclusion comes from the observation that the rsmB genes are much more effective as positive regulators in a RsmA(+) strain of E. carotovora subsp. carotovora than in its RsmA(−) derivative. E. herbicola pv. gypsophilae produces a 290-base rsmB transcript that is not subject to processing. By contrast, E. amylovora produces 430- and 300-base rsmB transcripts, the latter presumably derived by processing of the primary transcript as previously noted with the transcripts of rsmB(Ecc). Southern blot hybridizations revealed the presence of rsmB homologs in E. carotovora, E. chrysanthemi, E. amylovora, E. herbicola, E. stewartii and E. rhapontici, as well as in other enterobacteria such as Escherichia coli, Salmonella enterica serovar Typhimurium, Serratia marcescens, Shigella flexneri, Enterobacter aerogenes, Klebsiella pneumoniae, Yersinia enterocolitica, and Y. pseudotuberculosis. A comparison of rsmB sequences from several of these enterobacterial species revealed a highly conserved 34-mer region which is predicted to play a role in positive regulation by rsmB RNA.